Comparison of the Pharmacokinetics of Ketorolac Tromethamine After Continuous Subcutaneous Infusion and Repeat Intramuscular Bolus Injections in Healthy Adult Subjects. Issue 4 (11th January 2017) - Burdick, Michael; Mamelok, Richard; Hurliman, Michele; Dupuis, Mariève; Xie, Yuli; Grenier, Julie; Sheldon, Curtis; Gartner, Michael; Noymer, Peter
Abstract: Ketorolac tromethamine is a nonsteroidal anti‐inflammatory drug that exhibits analgesic activity with no sedative or anxiolytic properties. Twelve healthy male subjects were enrolled in a study to receive either of 2 treatments over 2 periods in an open‐label, randomized, 2‐way crossover design: (A) 120 mg of ketorolac tromethamine administered as a continuous subcutaneous infusion over a 24‐hour period; or (B) an identical total daily dose administered as 4 intramuscular bolus injections of 30 mg each given every 6 hours (current labeled treatment regimen). The pharmacokinetic and safety profiles were evaluated for both treatments. Both modes of administration have similar values for area under the curve (AUC) and half‐life (t1/2 ), suggesting that continuous subcutaneous infusion and repeated intramuscular bolus injections have similar bioavailability. The peak plasma concentration (Cmax ) was 40% lower when ketorolac was administered as a continuous subcutaneous infusion compared with repeat intramuscular bolus injections. The concentration at steady‐state (Css ) for continuous subcutaneous infusion was between the Cmax and Ctrough values obtained following the 4 intramuscular injections. Both treatment arms were well tolerated.